Continuous Production of Nanocrystalline TiO2 Nanofibers - Kejzlar, Pavel; Kovar, Radovan (Manufacturing Technology Journal, 2016)
Titanium dioxide in its anatase allotropic modification is well known for its photovoltaic and photocatalytic activity. Through a modification of Nanospider™ device it was achieved a continuous production of nanocrystaline anatase nanofibers. These inorganic fibres have a huge specific surface area due to their fine diameter and structure and thus offer a promising potential in many applications. In this article it is described the device allowing continuous production of inorganic TiO2 nanofibers by the use of electrospinning process and optimization of following calcination process leading to obtaining of almost pure nanocrystaline anatase structure.
Keywords: Anatase; Electrospinning; Nanofiber; NanospiderTM; Photocatalysis; Structure